Answer:
Given the statement: Square root 300c^9 = 10c^x square root 3 c
⇒
![√(300c^9) =10c^x√(3c)](https://img.qammunity.org/2020/formulas/mathematics/high-school/h2i1dvv4qnzousb9u9mhxnplwoa547wzu4.png)
Squaring both sides we get;
![(√(300c^9))^2= (10c^x√(3c))^2](https://img.qammunity.org/2020/formulas/mathematics/high-school/zcthkvkoqn2mgsb80m7lewvd3esjiw459h.png)
Simplify:
![300c^9 = 100c^(2x)(3c)](https://img.qammunity.org/2020/formulas/mathematics/high-school/mkhc8jnxkeu2hpxtorc6mclyaug5n9d20a.png)
We know:
![a^m \cdot a^n = a^(m+n)](https://img.qammunity.org/2020/formulas/mathematics/high-school/rcbggz13mw5jqp4bnmy9d39rlo6a4949y4.png)
then;
![300c^9 = 300c^(2x+1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/8xvdfks176ejxtnx8vv1iyifavjtbgp4wm.png)
Divide both sides by 300 we get;
![c^9 = c^(2x+1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ln8q3yoo45mcyzg0l8h1k3y0e65j28wfhj.png)
On comparing both sides we have;
![9 = 2x+1](https://img.qammunity.org/2020/formulas/mathematics/high-school/3fy4t2iujdf3cm35wgv68ex6hf9kje9rbf.png)
Subtract 1 from both sides we get;
8 = 2x
Divide both sides by 2 we have;
x = 4
Therefore, for the value of x =4 the given statement is true.